2000
DOI: 10.1143/jjap.39.3872
|View full text |Cite
|
Sign up to set email alerts
|

Location-Control of Large Si Grains by Dual-Beam Excimer-Laser and Thick Oxide Portion

Abstract: An array of large Si grains was placed at a predetermined position by dual excimer-laser irradiation of a multi-layer structure of silicon (Si), silicon dioxide (SiO2) with an array of bumps and metal on a glass substrate. We have investigated the effects of irradiating energy density and the topology of the structure on the grain size and crystallographic structure by scanning electron microscopy (SEM) and electron back-scattering pattern (EBSP) analysis. In the low-energy-density regime, numerous small grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Consequently, nonuniform and randomly distributed poly-Si grains will result in large variation of TFT performance when the laser energy density is controlled in the SLG regime, particularly, for smalldimension TFTs [13], [14]. Thus, many laser crystallization methods have been proposed to produce large grains with uniform grain size distribution, including sequential lateral solidification [15], the grain filters method [16], capping the reflective or antireflective layer [17], phase-modulated ELC [18], dual-beam excimer laser annealing (ELA) [19], double-pulsed laser annealing [20], selectively floating a-Si active layer [21], continuous-wave laser lateral crystallization [22], selectively enlarging laser crystallization [23], and so on. However, some of them are not readily attached to existing ELA systems or are problematic for circuit layout due to the anisotropy of the grain boundary spacing.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, nonuniform and randomly distributed poly-Si grains will result in large variation of TFT performance when the laser energy density is controlled in the SLG regime, particularly, for smalldimension TFTs [13], [14]. Thus, many laser crystallization methods have been proposed to produce large grains with uniform grain size distribution, including sequential lateral solidification [15], the grain filters method [16], capping the reflective or antireflective layer [17], phase-modulated ELC [18], dual-beam excimer laser annealing (ELA) [19], double-pulsed laser annealing [20], selectively floating a-Si active layer [21], continuous-wave laser lateral crystallization [22], selectively enlarging laser crystallization [23], and so on. However, some of them are not readily attached to existing ELA systems or are problematic for circuit layout due to the anisotropy of the grain boundary spacing.…”
Section: Introductionmentioning
confidence: 99%
“…The processing window of total energy density is not sufficiently wide in comparison with the pulse-to-pulse fluctuation of a modern commercial excimer laser machine. The energy density of SLG has a very narrow "processing window", typically approximately 2.5% [34] and 1.5% [35], respectively. The processing window was enhanced approximately 5% using the in situ TRORT measurements in this study.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that the location of the unmelted region can be controlled by the local modification of heat extraction rate towards the substrate. 4,5 The required number of the laser pulse is one, which is also the advantage in terms of the throughput. Although we confirmed that the position of the individual grains can be indeed accurately controlled in 3D manner, the issue of uniformly obtaining single-crystalline Si islands still remained.…”
Section: D Location-control Of Grains With Structural Variation By Pmentioning
confidence: 99%
“…4,5 In "µ-Czochralski process" 6 which uses local unmelting at a bottom of thick and narrow Si column (grain filter), grains with a diameter of 6 µm can be located at predetermined positions. TFTs fabricated inside such a grain, showed field-effect mobility for electrons of 450 cm 2 /Vs on average, 7, 8 which is well comparable to that of counterparts made with SOI wafers.…”
Section: Introductionmentioning
confidence: 99%